THE ROLE OF THE MILLENNIAL GENERATION IN EFFORTS TO PRESERVE CULTURE IN THE MIDST OF AN ERA OF TECHNOLOGICAL DISRUPTION - Dayningrum, Hayyum; Anggi Ritonga , Windy (International Journal of Students Education, 2023)
Seeing the fact that the industrial revolution 4.0 which caused technological disruption was marked by the development of the Internet of or for Things which caused changes in human lifestyles and had implications for the fading of ancestral culture. This research examines the role of the next generation in maintaining culture in the midst of technological disruption. The research method uses a qualitative approach and collects data using library research. The results of the business discussion that can be played by the millennial generation in an effort to maintain culture amidst currents of technological disruption are culture experience and culture knowledge.